Analisis Audit Kepatuhan Syariah dalam Membangun Kepercayaan Nasabah pada Bank Syariah - Lailatul Igna Syafaah; Lulu Il Mufidah; Fikri Rizki Utama (Indonesia Economic Journal, 2026)
Sharia compliance is the main pillar of Islamic banking integrity, yet public doubts regarding operational authenticity and auditor competency gaps remain strategic issues. This study aims to analyze the effectiveness of sharia compliance audits in building and maintaining customer trust in Islamic banks in Indonesia. The research method employed is descriptive qualitative, with data gathered through in-depth interviews with ten informants (six customers, two bank employees, and two academics) as well as a comprehensive literature review, analyzed using the Miles and Huberman model. The results indicate that regular sharia compliance audits supervised by the Sharia Supervisory Board (SSB) provide spiritual assurance and religious security for customers to avoid usury (riba). Although barriers persist regarding auditors' technical competencies and the complexity of audit report language for laypeople, transparency in report publication remains key to accountability. In conclusion, a credible sharia compliance audit aligned with excellent service quality is the most effective strategy to secure customer loyalty and foster long-term trust.